Diversity of Uropathogens and Ciprofloxacin Resistance Patterns Among Females of Different Age Groups in a Tertiary Care Hospital in Bangladesh - Afroz, Samira; Shazzad, Md Nahiduzzamane; Rahman, Asma; Lutfor, Afzalunnessa Binte; Rahman, Mahbubur (Journal of Medicine, 2025)
Introduction: Urinary tract infections (UTIs) are the most common bacterial infections globally, with a particularly high burden among females. Ciprofloxacin has long been a key antimicrobial for empirical UTI treatment, but increasing resistance raises concern, especially in regions with limited surveillance data.This study aimed to investigate the diversity of uropathogens and ciprofloxacin resistance patterns across different age groups of female patients in a tertiary care hospital in Bangladesh. Methods: A retrospective cross-sectional study was conducted from January to December 2022 at the Department of Microbiology,Ad-din Women’s Medical College Hospital, Dhaka. Midstream urine samples from the suspected female patients of UTI were cultured and analyzed using standard microbiological techniques. Antimicrobial resistance to ciprofloxacin was evaluated using the Kirby-Bauer disk diffusion technique, and the results were interpreted per the 2020 guidelines of the Clinical and Laboratory Standards Institute. Results: Out of 1930 samples, 323 (16.74%) were ciprofloxacin-sensitive, while 1607 (83.26%) were resistant. Most infections occurred in the 15–49 age group (67.88%). Escherichia coli was the most prevalent uropathogen (43.32%), followed by other staphylococci species, specifically coagulase-negative Staphylococci (OSS) (24.61%), and Enterobacter spp. (12.54%), and Klebsiella spp. (6.58%). Ciprofloxacin resistance was highest among Enterococci (96.97%), followed by Klebsiella spp. (88.19%) and E. coli (85.17%). Resistance was significantly higher in younger age groups (p < 0.0001). Conclusion:This study reveals alarmingly high ciprofloxacin resistance rates among uropathogens, particularly in reproductive-age females. The findings underscore the urgent need for local antibiotic stewardship, culture-guided therapy, and age-specific empirical treatment guidelines to combat rising antimicrobial resistance in Bangladesh. J MEDICINE 2025; 26(2): 117-123